2003
DOI: 10.1046/j.1439-0442.2003.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa L. and Urtica dioica L. on Lipid Peroxidation, Antioxidant Enzyme Systems and Some Liver Enzymes in CCl4‐Treated Rats

Abstract: This study was designed to investigate the effects Nigella sativa L. (NS) and Urtica dioica L. (UD) on lipid peroxidation, antioxidant enzyme systems and some liver enzymes in carbon tetrachloride (CCl4)-treated rats. A total of 60 healthy male Sprague-Dawley rats were utilized in this study. The rats were randomly allotted into one of four experimental groups: A (CCl4-only treated), B (CCl4 + UD treated), C (CCl4 + NS treated) and D (CCl4 + UD + NS treated), each containing 15 animals. All groups received CCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
151
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 24 publications
12
151
1
4
Order By: Relevance
“…Vessal et al suggested that QE supplementation has proven to be beneficial in decreasing blood glucose concentration, promoting regeneration of the pancreatic islets and increasing insulin release in STZ-induced diabetic rats; thus exerting its beneficial antidiabetic effects (23). The role and usage of natural antioxidants for preventing oxidative damage in DM is on the increase (3,16). QE had no significant hypoglycemic effect on normoglycemic rats, but, antagonizing the raising in blood sugar induced by STZ treated rats and this effect might be secondary to its antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Vessal et al suggested that QE supplementation has proven to be beneficial in decreasing blood glucose concentration, promoting regeneration of the pancreatic islets and increasing insulin release in STZ-induced diabetic rats; thus exerting its beneficial antidiabetic effects (23). The role and usage of natural antioxidants for preventing oxidative damage in DM is on the increase (3,16). QE had no significant hypoglycemic effect on normoglycemic rats, but, antagonizing the raising in blood sugar induced by STZ treated rats and this effect might be secondary to its antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential properties of NS is the ability of one or more of its constituents to reduce toxicity due to its antioxidant activities. The majority of studies that have been performed to evaluate the different effects of NS have been confined to address its antitoxic properties [9,10,26,27]. In addition to this, many investigators have determined the antioxidant activities of NS in vivo [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant and free radical scavenging properties of U. dioica leaves have been established by several studies (Kanter et al, 2005;Cetinus et al, 2005;Mavi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This herb is known for its anti-inflammationtory activity (Obertries et al, 1996;Riehemann et al, 1999). There have been also other reports indicating the benefits of using the extract of the leaves or other parts for the use in different conditions, i.e., diabetes (Kavalali et al, 2003;Román Ramos et al, 1992;Petleveski et al, 2003;Farzami et al, 2003) as well as other disorders like prostatic hyperplasia (Hirano et al, 1994;Lichius & Muth, 1997;Kayser et al, 1995), rheumatoid arthritis, hypertension and allergic rhinitis (Mittman, 1990), stimulation of human lymphocytes (Wagner et al, 1989) and decreasing the lipid peroxidation and liver enzymes (Kanter et al, 2003).…”
Section: Introductionmentioning
confidence: 88%